Expecting the unexpected: measures, outcomes and dying trajectories for expected and unexpected death in adults with intellectual disabilities in social care settings in the UK. Issue 2 (30th November 2020) - Bernal, Jane; Hunt, Katherine; Worth, Rhian; Shearn, Julia; Jones, Edwin; Lowe, Kathy; Todd, Stuart
Abstract: Background: Considerable attention is rightly paid to preventable deaths in adults with intellectual disabilities. The pattern of these deaths and the implications for services have been less considered. Method: This paper forms part of a larger cross‐sectional study of deaths in a defined population of adults with intellectual disabilities. Data from VOICES‐SF were obtained from intellectual disability service providers for each death within their supported population over 18 months, 149 decedents in all. Results: Only 34.2% of deaths were anticipated, death was often sudden or followed a short illness. Four dying trajectories were identified, and categorized by length of illness, service use, care outcomes, symptom control and cause of death. Conclusions: Recognition that most deaths in this group were unanticipated implies a need for better preparation for less expected dying and better anticipation. A descriptive epidemiology of dying among people with intellectual disabilities is needed.